الوظائف الثقافية في سردية الهامش رواية (ساق الفرس) ضياء جبيلي اختياراً - Ismail Abdual-Kareem, Lect . Dr. Walaa (Basra studies journal, 2025)
The margin constitutes a significant concern in societies, and at the same time, it cannot have any significance; rather, it is a margin that can be pushed aside at any moment. This issue between anxiety and displacement makes the existence of marginalized societies a narrative material worthy of inclusion. This is what the Iraqi storyteller Diaa Jubaili did in his novel "The Horse's Leg," which symbolizes a woman who loses much of her existence. The research initially addressed the main research concepts (the model, the margin, the cultural function), and then by examining the novel led the researcher to contemplate three functions, each linked to a dominant element. The social function was associated with the narrator/Saleema, who tried to confront societal norms and systems, and how the margin can either confront these norms or justify their existence. The second function, which is gender-related, was connected to the protagonist of the novel (Abeer), who suffers from disturbances in sexual identity and seeks a sexual/gender alternative. The third function is the interpretive function related to society, particularly the neighborhood community, which represents a metaphor for Iraqi or Basra society, where the novel interpreted some phenomena that affected the community.